Collaboration and Social Interaction in Mathematics Learning in Multicultural Classrooms: A Qualitative Case Study - Rina Agustina; Selvi Loviana (Jurnal Pendidikan Matematika Universitas Lampung, 2026)
Mathematics learning in multicultural classrooms requires collaborative interaction that accommodates students’ cultural and linguistic diversity. This study aims to explore how cultural diversity shapes collaboration and social interaction in mathematics learning in a multicultural classroom. This study employed a qualitative case study design. The participants were 16 undergraduate mathematics education students at a private university in Metro City, Indonesia. The classroom was categorized as multicultural because the students came from different cultural backgrounds and showed variations in language use, communication styles, ways of expressing opinions, and approaches to group discussion and mathematical problem solving. Data were collected through questionnaires, semi-structured interviews, participatory observation, and documentation. The questionnaire covered three aspects: students’ experiences and perceptions of multicultural classrooms, group dynamics in mathematical problem solving, and collaborative projects in mathematics learning. The data were analyzed through data reduction, categorization, interpretation, and conclusion drawing, with source and technique triangulation used to strengthen the credibility of the findings. The results show that cultural diversity did not directly determine students’ mathematical problem-solving ability, which was more strongly influenced by their understanding of the material. However, cultural diversity affected the communication process, discussion dynamics, and ways students expressed mathematical ideas. Differences in language, thinking styles, and communication patterns became the main challenges in group interaction. Nevertheless, most students were able to collaborate with peers from different cultural backgrounds. These findings indicate that multicultural mathematics classrooms require inclusive interaction strategies, heterogeneous grouping, and clear classroom communication to support effective collaboration and social interaction.